Arbitration as a Solution System of Disputes in the Contemporary Cultural Context in Peru and Latin American of 21st Century - Sumaria Benavente, Omar (2015)
The state space inertia and lack of comprehensive strategies for reform of the justice system that cause the inefficiency of the state system of dispute resolution opens the way for new forms of private initiative and is arbitration which replaces the State satisfying this need for compliance with the law. However, the inefficiency of the state system for conflict resolution is not the only cause, and the “cultural context” is a major element in the development of ADRs directly dependent changes in conflicting values at the end of the century XX, distrust in government, privatization, the humanization of large-scale institutions, social progress through individual improvement, and postmodern skepticism that a culture based on freedom, individualism, populism, equality are identified, liberalism, utilitarianism considering that the procedures used to resolve controversies are rooted in the culture of society.